2018
DOI: 10.3390/su10040948
|View full text |Cite
|
Sign up to set email alerts
|

Phase Change Material (PCM) Application in a Modernized Korean Traditional House (Hanok)

Abstract: Social and policy interest in the modernization and revitalization of the Korean traditional house (Hanok) has increased recently in Korea but its low thermal performance is one of its weaknesses. A feasibility study was conducted to evaluate the suitability of a Phase Change Material (PCM) in a modernized Hanok. The research method involved a test of the heating and cooling load reduction and Predicted Mean Vote (PMV) analysis for human comfort using an Esp-r simulation adopting multi variable PCM types as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Previous studies, however, show that there is a lack of complex interest in the integrated evaluation system and detailed guidelines in terms of sustainability toward open innovation including the spatial comfort. Lee and Park, in this sense, raised some critical issues for Hanok have emerged, such as narrow space dimensions and the layout for a modern lifestyle, poor insulation, weak fire resistance, expensive construction costs and so on, in comparison to contemporary buildings [47,48].…”
Section: Discussion; Innovation In Hanok and Open Innovationmentioning
confidence: 99%
“…Previous studies, however, show that there is a lack of complex interest in the integrated evaluation system and detailed guidelines in terms of sustainability toward open innovation including the spatial comfort. Lee and Park, in this sense, raised some critical issues for Hanok have emerged, such as narrow space dimensions and the layout for a modern lifestyle, poor insulation, weak fire resistance, expensive construction costs and so on, in comparison to contemporary buildings [47,48].…”
Section: Discussion; Innovation In Hanok and Open Innovationmentioning
confidence: 99%
“…As regards the opaque envelope, six articles studied the impact of implementing passive solutions, such as phase change materials (PCM), green roofs, dynamic insulations, high-performance insulation materials and sunshades, flexible canopies and Prefabricated Straw Bale Construction (PSBL), on building energy performance and saving [24][25][26][27][28][29].…”
Section: A Short Review Of the Contributions To This Special Issuementioning
confidence: 99%
“…Lee et al [24] used Esp-r simulation software to evaluate the heating and cooling load reduction and Predicted Mean Vote (PMV) for human comfort adopting multi variable PCM types as the building wall composite in a modernized Korean Hanok. They concluded that PCM helps reduce energy consumption also of 53.1%.…”
Section: A Short Review Of the Contributions To This Special Issuementioning
confidence: 99%
“…To compensate for these problems, modern materials, such as insulation and glass windows, are applied. Through this, analysis shows that the energy load of hanok can be reduced by up to 73%, and the future value is also expected to be promising [14]. Since hanok is an ecological building that reflects cultural and social contexts, such as human and nature, changes in the intrinsic value of the materials should be avoided.…”
Section: Introduction 1backgroundmentioning
confidence: 99%